ASME 2008 6th International Conference on Nanochannels, Microchannels, and Minichannels 2008
DOI: 10.1115/icnmm2008-62134
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flow Modeling in Microchannels and Minichannels

Abstract: In the present paper, three different methods for two-phase flow modeling in microchannels and minichannels are presented. They are effective property models for homogeneous two-phase flows, an asymptotic modeling approach for separated two-phase flow, and bounds on two-phase frictional pressure gradient. In the first method, new definitions for two-phase viscosity are proposed using a one dimensional transport analogy between thermal conductivity of porous media and viscosity in two-phase flow. These new defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…8e, which locally alters the forces between fluid and discs. The higher viscous heating contributes to a higher formation of flow vortices, reported by Alonso et al 2019 [54] for turbulent flows. The velocity field is shown in Fig.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…8e, which locally alters the forces between fluid and discs. The higher viscous heating contributes to a higher formation of flow vortices, reported by Alonso et al 2019 [54] for turbulent flows. The velocity field is shown in Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The two-dimensional numerical model for assessing the fluid dynamics of the two-phase Tesla turbine was developed in the EES environment [30]. It combines the single-phase model of the Tesla turbine, set in previous studies [12,20], and the two-phase homogeneous model [52], where the same velocities of the two phases (gas and liquid) are assumed ( ) [53,54] The following assumptions were considered:…”
Section: Methodology Homogeneous Modelmentioning
confidence: 99%
“…Over time, this method of combining asymptotic solutions proved quite to be successful in developing models in many applications. Recently, it has been applied to two-phase flow in circular pipes (Awad, 2007;Muzychka and Awad, 2010), minichannels (Awad, 2007;Muzychka and Awad, 2010;Awad and Muzychka, 2010), and microchannels (Awad, 2007;Muzychka and Awad;2010). Moreover, Awad and Butt (2009a,b,c) have shown that the asymptotic method works well in petroleum industry applications for flows through porous media, liquid-liquid flows, and flows through fractured media.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…A discussion critically examined the sensitivity of the performance of the model to the three optimised parameters (confined bubble frequency, initial film thickness and end film thickness) and some preliminary investigation relating the critical film thickness for dryout to measured tube roughness. Awad and Muzychka [75] used three incomparable models in order to simulate two-phase flows in microchannel and minichannels. The first method introduces a new description to two-phase viscosity by the help of one-dimensional analogy between two phase flow viscosity and porous media thermal conductivity.…”
Section: Microchannel Geometrymentioning
confidence: 99%